Nonlinear Adaptive Control of a pH Process - K. Al-Dawery, Salam; Ali Omran Al-Anbari, Hameed; Fadhel Ahmed, Duraid (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
In this paper a nonlinear adaptive control method is presented for a pH process, which is difficult to control due to the nonlinear and uncertainties. A theoretical and experimental investigation was conducted of the dynamic behavior of neutralization process in a continuous stirred tank reactor (CSTR). The process control was implemented using different control strategies, velocity form of PI control and nonlinear adaptive control. Through simulation studies it has been shown that the estimated parameters are in good agreement with the actual values and that the proposed adaptive controller has excellent tracking and regulation performance.